(untitled) (Research, Society and Development, 2021)
Surgical Site Infection (SSI) is defined as an infectious process in which it affects the tissues, cavities and organs covered in surgical procedures, requiring a special effort to keep them under control, being called quality control parameters in the service. provided by a hospital institution. The objective of this article was to describe the nursing conducts and management aimed at reducing surgical site infections and patient safety in nursing care. The review, after the readability and ineligibility process, selected 12 articles through exploratory, selective, analytical and interpretive reading, from the LILACS and SCIELO databases. The selected researches provided us with a quantity of 320 possible works for the desired study, thus, there were 30 and after reading again these abstracts that were available in full and that, consequently, were reread and selected again, a number of 12 studies that met the objective of this review study. Thus, it was emphasized the need for implementation of educational measures that reach all care professionals who work in this context, seeking not only awareness, but also the recognition and application of scientific knowledge in professional practice, making this a fundamental artifice in combat to routine infection.